Enteral nutrition for maintenance of remission in Crohn's disease - Akobeng, Anthony K (Cochrane Database Syst Rev, 2018)
BACKGROUND: Prevention of relapse is a major issue in the management of quiescent Crohn's disease (CD). Current therapies (e.g. methotrexate, biologics, 6‐mercaptopurine and azathioprine) may be effective for maintaining remission in CD, but these drugs may cause significant adverse events. Interventions that are effective and safe for maintenance of remission in CD are desirable. OBJECTIVES: The primary objectives were to evaluate the efficacy and safety of enteral nutrition for the maintenance of remission in CD and to assess the impact of formula composition on effectiveness. SEARCH METHODS: We searched MEDLINE, Embase, CENTRAL, the Cochrane IBD Group Specialized Register and clinicaltrials.gov from inception to 27 July 2018. We also searched references of retrieved studies and reviews. SELECTION CRITERIA: Randomised controlled trials (RCTs) including participants of any age with quiescent CD were considered for inclusion. Studies that compared enteral nutrition with no intervention, placebo or any other intervention were selected for review. DATA COLLECTION AND ANALYSIS: Two authors independently screened studies for inclusion, extracted data and assessed methodological quality using the Cochrane risk of bias tool. The primary outcome was clinical or endoscopic relapse as defined by the primary studies. Secondary outcomes included anthropometric measures (i.e. height and weight), quality of life (QoL), adverse events, serious adverse events and withdrawal due to adverse events. We calculated the risk ratio and 95% confidence interval (CI) for dichotomous outcomes. For continuous outcomes, we calculated the mean difference and 95% CI. A random‐effects model was used for the statistical analysis. We used the GRADE criteria to assess the overall certainty of the evidence supporting the primary outcome and selected secondary outcomes. MAIN RESULTS: Four RCTs (262 adult participants) met the inclusion criteria. One study (N = 33) compared an elemental diet to a non‐elemental (polymeric) diet. One study (N = 51) compared a half elemental diet to a regular free diet. Another study (N = 95) compared an elemental diet to 6‐mercaptopurine (6‐MP) or a no treatment control group. One study (N= 83) compared a polymeric diet to mesalamine. Two studies were rated as high risk of bias due to lack of blinding or incomplete outcome data. The other two studies were judged to have an unclear risk of bias. The studies were not pooled due to differences in control interventions and the way outcomes were assessed. The effect of an elemental diet compared to a polymeric diet on remission rates or withdrawal due to adverse events is uncertain. Fifty‐eight per cent (11/19) of participants in the elemental diet group relapsed at 12 months compared to 57% (8/14) of participants in the polymeric diet group (RR 1.01, 95% CI 0.56 to 1.84; very low certainty evidence). Thirty‐two per cent (6/19) of participants in the elemental diet group were intolerant to the enteral nutritional formula because of taste or smell and were withdrawn from the study in the first 2 weeks compared to zero participants (0/14) in the polymeric diet group (RR 9.75, 95% CI 0.59 to 159.93; low certainty evidence). Anthropometric measures, QoL, adverse events and serious adverse events were not reported as outcomes. The effect of an elemental diet (half of total daily calorie requirements) compared to a normal free diet on relapse rates is uncertain. Thirty‐five per cent (9/26) of participants in the elemental diet group relapsed at 12 months compared to 64% (16/25) of participants in the free diet group (RR 0.54, 95% CI 0.30 to 0.99; very low certainty evidence). No adverse events were reported. This study reported no differences in weight change between the two diet groups. Height and QoL were not reported as outcomes. The effect of an elemental diet compared to 6‐MP on relapse rates or adverse events is uncertain. Thirty‐eight per cent (12/32) of participants in the elemental diet group relapsed at 12 months compared to 23% (7/30) of participants in the 6‐MP group (RR 1.61; 95% CI 0.73 to 3.53; very low certainty evidence). Three per cent (1/32) of participants in the elemental diet group had an adverse event compared to 13% (4/30) of participants in the 6‐MP group (RR 0.23, 95% CI 0.03 to 1.98; low certainty evidence). Adverse events in the elemental diet group included surgery due to worsening CD. Adverse events in the 6‐MP group included liver injury (n = 2), hair loss (n = 1) and surgery due to an abscess (n = 1). No serious adverse events or withdrawals due to adverse events were reported. Weight, height and QoL were not reported as outcomes The effect of a polymeric diet compared to mesalamine on relapse rates and weight is uncertain. Forty‐two per cent (18/43) of participants in the polymeric diet group relapsed at 6 months compared to 55% (22/40) of participants in the mesalamine group (RR 0.76; 95% CI 0.49 to 1.19; low certainty evidence). The mean difference in weight gain over the study period was 1.9 kg higher in the polymeric diet group compared to mesalamine (95% CI ‐4.62 to 8.42; low certainty evidence). Two participants in the polymeric diet group experienced nausea and four had diarrhoea. It is unclear if any participants in the mesalamine group had an adverse event. Height, QoL, serious adverse events and withdrawal due to adverse events were not reported as outcomes. AUTHORS' CONCLUSIONS: The results for the outcomes assessed in this review are uncertain and no firm conclusions regarding the efficacy and safety of enteral nutrition in quiescent CD can be drawn. More research is needed to determine the efficacy and safety of using enteral nutrition as maintenance therapy in CD. Currently, there are four ongoing studies (estimated enrolment of 280 participants). This review will be updated when the results of these studies are available.